Research on the Critical Temperature and Stage Characteristics for the Spontaneous Combustion of Different Metamorphic Degrees of Coal. Issue 5 (4th July 2018) - Qu, Lina; Song, Dazhao; Tan, Bo
ABSTRACT: In this article, thermal gravimetric analysis and Fourier infrared-spectrum technology were used to analyze the change rules for the critical temperature and stage characteristics during a coal's spontaneous-combustion oxidation-reaction process. Different-metamorphic-degree-coal change rules and influence factors of the characteristic temperatures were studied. The characteristics of the coal temperature showed an increase trend with an increase of the heating rate. The characteristics of the coal temperature decreases; when the heating rate and oxygen concentration were different, the value of the characteristic temperature was anthracite > bituminous > lignite. The critical temperature of the coal's functional characteristic peak-absorption strength was related to the coal metamorphic degree. Variation characteristics about the changes of the coal's functional characteristic peak-area values and the coal functional groups' characteristic peak-absorption intensity were similar. The changing trend was an increase with a decrease firstly, then a decrease and an increase again. The microcritical temperature of the coal's functional groups was the refinement of the coal's functional macrochanging trend, and the change trends were consistent with the macrocritical temperature-changing trend. The macropoint of the coal functional groups' characteristic peak-absorption strength can be used as a new method to determine the critical temperature of the spontaneous combustion of coal.